Changes in the Recording of Cash-Based Accounting Methods to Accrual Base - Dian Islamiatus Sa'diyah; Indrawati Yuhertiana (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to determine changes in public sector accounting from cash basis to accrual basis and which one is better than the two bases. This study uses a qualitative method through literature study that combines a number of reliable data sources such as journals, books, articles, legislation, research results and those relevant to the problem being studied, where 12 of the 42 articles were selected and published between the 2013-2018 period. . The change in cash basis reform towards accruals consists of 3 phases, namely the pre-autonomy era, the transition era and the post-regional autonomy era. Of the two bases, the accrual basis is better because the accrual basis produces more transparent accounting reports for the sake of realizing good governance.